Perancangan Sistem Pembangkit Listrik Tenaga Surya (PLTS) Off-Grid Pada Gedung Perkuliahan: Design of Off-Grid Solar Power Plant System (PLTS) in Lecture Building - Fauzsan, Achmad Yamani; Yunesti, Putty; Wardani, Wulan Kusuma; Soelami, FX Nugroho; Friansa, Koko; Bangun Persada, Guna; Wira Buana, Setiadi (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Off-Grid Solar Power Plant (PLTS) system planning at Building F of the Sumatra Institute of Technology, South Lampung Regency, Lampung Province is one of the efforts or strategies in reducing the use of conventional electrical energy from the main supplier, namely the State Electricity Company (PLN), and helping to succeed the government's efforts to increase the consumption of new and renewable energy. In PLTS system planning, the aspects that will be analyzed in this research are technical aspects with the help of PVsyst software to collect data regarding technical indicators such as performance ratios and energy production generated by Off-Grid PLTS. In this research, the required land area is 52 m2 from a total of 930 m2 of available land. The simulation results show that the planned rooftop solar system has a capacity of 10.8 kWp using 24 units of AE SOLAR MC144 430-450 W type solar modules, with the capacity of each module being 450 Wp. The PLTS system uses 1 inverter with the type Victron Quattro 48/15000 (15 kW) with a capacity of 15,000 W and uses a battery with the type LUNA2000-15- S0 which has a capacity of 15 kW in each unit. In this study, the solar module received solar irradiation of 4,616 kWh/m2 per day and 1,684 kWh/m2 per year. The production obtained in this study amounted to 14,475 kWh per year. The percentage of the Performance Ratio (PR) value produced by the designed OffGrid PLTS system is 73.01%.